Pengaruh Kompensasi terhadap Kinerja Karyawan pada Dinas Perumahan Rakyat dan Kawasan Permukiman Kabupaten Nias - Ndruru, Bernada; Hulu, Fatolosa; Baene, Eduar; Harefa, Idarni (Jurnal EMT KITA, 2025)
. Compensation is one of the important factors that influence employee behavior and performance. Higher compensation levels tend to improve employee welfare. This study aims to analyze the effect of compensation, which includes salary, allowances, and incentives, on employee performance at the Public Housing and Settlement Area Service of Nias Regency. The phenomena observed include decreased work motivation, decreased attendance discipline, and failure to achieve work targets. This study uses a quantitative approach with data analysis through SPSS software. The research sample consisted of 30 respondents who were all employees of the agency. The results of the analysis showed a significant effect between compensation and performance, where the validity test of variables X and Y showed a calculated r value of 0.742, higher than the r table of 0.361. The average compensation score was 6.42 and the average performance score was 7.24, both of which were included in the good category. In conclusion, compensation has a significant effect on employee performance, so that it can increase work motivation and productivity. These findings emphasize the importance of effective compensation management to support improved individual and organizational performance.